PENGARUH MEDIA SOSIAL WHATSAPP TERHADAP KINERJA KARYAWAN MERCHANDISER PROMOTION SPECIALIST DI AGENCY PT GELATIK SUPRA PEKANBARU - Sahira Nadia Eka Putri; Rumyeni " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2022)
Communication is an inseparable part of human life. In an organization, communication plays a very important role, where communication is used for social interaction between members in the organization, both between superiors and subordinates, between divisions and colleagues in one unit. The WhatsApp application is not only used to communicate and exchange messages, but currently WhatsApp is also used for work purposes. This type of research is an expansive quantitative research, the sample in this study is employees who work in the Agency at PT Gelatik Supra Pekanbaru totaling 98 people, obtained by means of total sampling technique. The data obtained using a questionnaire distributed to employees at the Agency PT Gelatik Supra Pekanbaru then tested using SPSS version 23 software for windows. The results of hypothesis testing in this study using a simple linear obtained Y = 20.167+0.308 X while tcount (3.012) is greater than ttable (1.98). Based on the statistical calculations obtained, the hypothesis for this research is that Ha there is a significant influence between WhatsApp social media (X) employee performance (Y). Then it means that Ha is accepted and H0 is rejected. Furthermore, the coefficient of determination (Rsquare) is 0.86. This means that it can be explained that the performance of employees at PT Gelatik Supra Pekanbaru is 86%. influenced by social media whatsapp while the rest is influenced by other variables not examined in this study.